2019
DOI: 10.1017/dmp.2019.41
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Local Health Departments in Disaster Research: A Washington State Survey

Abstract: Objective:Disaster research can inform effective, efficient, and evidence-based public health practices and decision making; identify and address knowledge gaps in current disaster preparedness and response efforts; and evaluate disaster response strategies. This study aimed to identify challenges and opportunities experienced by Washington State local health departments (LHDs) regarding engagement in disaster research activities.Methods:An online survey was disseminated to the emergency preparedness represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The literature concerning Extension professionals in disaster response point to field work in one form or another (Kerr et al, 2018;Telg et al, 2007Telg et al, , 2008. Data collection allows disaster response teams to make informed decisions with clients (Bonanno et al, 2010;Everhart et al, 2019;Merwaday et al, 2016). Additionally, data collection helped with accessing resources from stakeholders, like state or national funds (Chen et al, 2006;Downey et al, 2018;McLean & Whang, 2019).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…The literature concerning Extension professionals in disaster response point to field work in one form or another (Kerr et al, 2018;Telg et al, 2007Telg et al, , 2008. Data collection allows disaster response teams to make informed decisions with clients (Bonanno et al, 2010;Everhart et al, 2019;Merwaday et al, 2016). Additionally, data collection helped with accessing resources from stakeholders, like state or national funds (Chen et al, 2006;Downey et al, 2018;McLean & Whang, 2019).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…The literature concerning Extension professionals in disaster response point to field work in one form or another (Kerr et al, 2018;Telg et al, , 2008. Data collection allows disaster response teams to make informed decisions with clients (Bonanno et al, 2010;Everhart et al, 2019;Merwaday et al, 2016). Additionally, data collection helped with accessing resources from stakeholders, like state or national funds (Chen et al, 2006;Downey et al, 2018;McLean & Whang, 2019).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…A survey of local health departments in Washington State found that one in 6 respondents (17%) had disaster research experience, citing funding and multiple priorities as barriers; this experience could be useful in designing, fielding, and interpreting the results of a community assessment for preparedness. 10 The purpose of this article is to describe how health department officials can use data collected from community assessments to drive toward intended outcomes to improve community radiological and other emergency preparedness. This includes an example approach for implementing the results through preparedness communication campaigns, policies, and exercises.…”
mentioning
confidence: 99%
“…Capacity for conducting assessments and evaluations is also a challenge. A survey of local health departments in Washington State found that one in 6 respondents (17%) had disaster research experience, citing funding and multiple priorities as barriers; this experience could be useful in designing, fielding, and interpreting the results of a community assessment for preparedness 10…”
mentioning
confidence: 99%